SARS-CoV-2: Cross-scale Insights from Ecology and Evolution. Issue 7 (July 2021) - Snedden, Celine E.; Makanani, Sara K.; Schwartz, Shawn T.; Gamble, Amandine; Blakey, Rachel V.; Borremans, Benny; Helman, Sarah K.; Espericueta, Luisa; Valencia, Alondra; Endo, Andrew; Alfaro, Michael E.; Lloyd-Smith, James O.
Abstract : Ecological and evolutionary processes govern the fitness, propagation, and interactions of organisms through space and time, and viruses are no exception. While coronavirus disease 2019 (COVID-19) research has primarily emphasized virological, clinical, and epidemiological perspectives, crucial aspects of the pandemic are fundamentally ecological or evolutionary. Here, we highlight five conceptual domains of ecology and evolution – invasion, consumer-resource interactions, spatial ecology, diversity, and adaptation – that illuminate (sometimes unexpectedly) the emergence and spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We describe the applications of these concepts across levels of biological organization and spatial scales, including within individual hosts, host populations, and multispecies communities. Together, these perspectives illustrate the integrative power of ecological and evolutionary ideas and highlight the benefits of interdisciplinary thinking for understanding emerging viruses. Highlights: Foundational concepts from ecology and evolution can elucidate the emergence and spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and all viruses, across multiple scales. Ecological and evolutionary methods that characterize population dynamics of organisms are potent tools to investigate viral growth and spread within individual hosts, or epidemic growth in host populations. The field of macroevolution classically studies the diversification and adaptation of multicellular organisms, but major opportunities exist to apply macroevolutionary concepts to the evolution of viruses. Concepts from spatial ecology, from source-sink dynamics to synchrony, can help us to understand patterns and processes in the emergence of viruses. Interdisciplinary research across the life sciences can reveal otherwise unattainable insights into emerging infectious diseases, posing new hypotheses and refining existing knowledge in traditional disciplines.